2020
DOI: 10.1186/s12916-020-01617-7
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and smoking cessation—a population survey in England

Abstract: Background: To reduce inequalities between individuals with and without mental health problems, a better understanding is required of triggers and success of quit attempts among the third of smokers with mental health problems. The aim was to assess whether there are differences by mental health status in (i) triggers for quit attempts, (ii) use of evidence-based support (iii) and quit success. Methods: Monthly cross-sectional household surveys of representative samples of the adult population in England. In 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Specific challenges such as higher dependence on tobacco need to be addressed by making effective support available. A combination of behavioural support and medication is most effective in the wider population of smokers and has been shown to be effective for smokers with severe mental illness [14,15] and for smokers with and without mental health problems making quit attempts [40]. In quit attempts and accompanied by behavioural support, e-cigarettes have been shown to be more effective than NRT [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific challenges such as higher dependence on tobacco need to be addressed by making effective support available. A combination of behavioural support and medication is most effective in the wider population of smokers and has been shown to be effective for smokers with severe mental illness [14,15] and for smokers with and without mental health problems making quit attempts [40]. In quit attempts and accompanied by behavioural support, e-cigarettes have been shown to be more effective than NRT [41].…”
Section: Discussionmentioning
confidence: 99%
“…In quit attempts and accompanied by behavioural support, e-cigarettes have been shown to be more effective than NRT [41]. In the Smoking Toolkit Study, they were also associated with increased success rates for smokers with and without mental health problems [40]. Additionally, smaller studies in smokers with severe mental illness who were not interested in quitting found that substantial proportions reduced their smoking by at least 50% when supplied with e-cigarettes [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…-cigarettes have been heralded as effective tools for smoking cessation. 1 Cross-sectional analyses 2 and RCTs 3 show that e-cigarettes both are associated with and lead to superior smoking-cessation outcomes. That said, public health organizations and policymakers vary in whether they have embraced or resisted these products, due, in part, to uncertainties about the consequences of prolonged use.…”
mentioning
confidence: 99%
“…Speci c challenges such as higher dependence on tobacco need to be addressed by making effective support available. A combination of behavioural support and medication is most effective in the wider population of smokers and has been shown to be effective for smokers with severe mental illness (14,15) and for smokers with and without mental health problems making quit attempts (40). In quit attempts and accompanied by behavioural support, e-cigarettes have been shown to be more effective than NRT (41).…”
Section: Discussionmentioning
confidence: 99%